2018
DOI: 10.1177/0361198118794052
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis on Performance of Severe Crash Prediction Methods

Abstract: The objective of this paper is to compare the performance and tradeoffs between two alternative analysis methods for developing crash prediction models for severe crashes: a direct estimation of severe crashes using frequency models, and an indirect but popular approach of combining frequency of total crashes models and some form of severity distribution functions (SDFs). The researchers conducted a comprehensive comparison of these modeling methods to illustrate the strengths and weaknesses of each alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The results suggested that the SDF approach outperforms the approach of developing separate models for each injury severity category. More recently, Avelar et al, (2018) conducted a comparative analysis on performance of severe crash prediction alternatives to illustrate the strengths and weaknesses of each method. A comparison was made and it was found that the performance of direct estimation of severe crashes was similar to that of using the SDF approach.…”
Section: Predicting Crash Frequency By Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that the SDF approach outperforms the approach of developing separate models for each injury severity category. More recently, Avelar et al, (2018) conducted a comparative analysis on performance of severe crash prediction alternatives to illustrate the strengths and weaknesses of each method. A comparison was made and it was found that the performance of direct estimation of severe crashes was similar to that of using the SDF approach.…”
Section: Predicting Crash Frequency By Severitymentioning
confidence: 99%
“…Examples of the development and application of the SDF approach includeShea et al (2015), Dixon et al (2015 andAvelar et al (2018). Other notable examples are cited in Chapter 3.…”
mentioning
confidence: 99%
“…The results suggested that the SDF approach outperforms the approach of developing separate models for each injury severity category. More recently, Avelar et al, (2018) conducted a comparative analysis on performance of severe crash prediction alternatives to illustrate the strengths and weaknesses of each method. A comparison was made and it was found that the performance of direct estimation of severe crashes was similar to that of using the SDF approach.…”
Section: Predicting Crash Frequency By Severitymentioning
confidence: 99%
“…Examples of the development and application of the SDF approach includeShea et al (2015), Dixon et al (2015 andAvelar et al (2018). Other notable examples are cited in Chapter 3.…”
mentioning
confidence: 99%